A Semantic Survey on Modal Verbs in Todays' Persian Language from a Typological Point of View - Shahla Sharifi; Narjes Banou Sabouri (نشریه پژوهش‌های زبان‌شناسی, 2021)
AbstractThis study aimed at investigating the semantic aspect of modal verbs in today’s Persian language from a typological perspective, which provided us with an opportunity to compare the meanings of Persian modal verbs with those of the other languages. The theoretical framework of this study belonged to Nauze (2008). This was a qualitative research, which was done using a descriptive-analytic method. The research data, which included natural Persian utterances, were obtained from texts appeared in the cyberspace. The modal verbs considered were as follows: bâyestan, tavânestan, šodan, and xâstan. After gathering the data, the type and semantic map of each modal verb were determined based on the conceptual space of modality presented by Nauze (2008). The results showed that Nauze’s modality framework could cover a variety of meanings of modal verbs in Today’s Persian language. It was also found that Today’s Persian data were in concordance with typological principle of Nauze, who claimed that all the meanings of modal verbs had to be based on one of the vertical axes.Keywords: Modality, Modal Verb, Semantic Map, Conceptual Space, Nauze’s Framework, Today’s Persian Language IntroductionModality is a category that has attracted the attention of many linguistics from different perspectives. However, it is said that providing a comprehensive, transparent, and clear definition of modality is difficult. In addition, modality can be represented in the syntactic-lexical construction of a language in the form of modal verbs, clauses, auxiliaries, adverbs, adjectives, or a combination of them. Thus, it covers a wide range of areas. The purpose of this study was to investigate Persian modal verbs from a semantic perspective using a typological framework. The research questions were as follows: What meanings did the modal verbs of bayestæn (must), tavanestæn (to be able), šodæn (to become), and xastæn (to want) have in the contemporary Persian language based on Nauze’s typological framework? Was this framework sufficient to cover the meanings of the given modal verbs? Was this typological principle that Nauze had proposed (all meanings of a modal verb are placed on one of the (vertical or horizontal) axes) true about the meanings of Persian modal verbs? Materials and MethodsThe present study was a qualitative research based on a descriptive-analytical method. The modal verbs of the contemporary Persian language in this study include four verbs of bayestæn (must), tavanestæn (to be able), šodæn (to become), and xastæn (to want). The verb of šayestæn (to deserve) was not included in this study as there was an agreement on its modality in the linguistic community and seemed to have been mostly used as an adverb today. To provide some natural data, the examples of the use of these verbs were searched through the Internet in the cyberspace, categorized based on their intended meanings, and then placed in the conceptual space of Nauze’s modality.The meanings of the verbs were first recognized in the examples based on the researchers’ linguistic tuition. In the next step, the examples were given to 20 linguistic students, who were asked to specify the meanings of the modal verbs in them. The second step was taken to ensure correct recognition of the meanings of the modal verbs. When there was a disagreement (not much in this study), the final analysis was done based on the majority of the analysts’ views. Discussion of Results & ConclusionsAssessment of the semantic mapping of the contemporary Persian modal verbs showed that bayestæn (must) had a semantic diversity only on the vertical axis of “necessity” and all its meanings were characterized on this axis. On the contrary, tavanestæn (to be able) covered all the modal meanings in Nauze’s conceptual space and was on the vertical axis of “possibility”. The modal verb of šodæn (to become) was like tavanestæn (to be able), which covered all the meanings in Nauze’s conceptual space on the vertical axis of “possibility”. However, xastæn (to want) had less semantic diversity than the other verbs and its only meaning was the dynamic aspect of internal participation that was on the axis of possibility.The semantic diversity of the mentioned contemporary Persian modal verbs can be generally demonstrated as follows:bayestæn/ tavanestæn /šodæn>xastæn Thus, bayestæn, tavanestæn, and šodæn convey most of modal meanings, while xastæn has modal meanings only in contemporary Persian. Three of these modal verbs had modal meanings on the vertical axis of “possibility”, while only one verb had its modal meaning on the axis of “necessity”. The two verbs of bayestæn and tavanestæn had modal usage in the Middle Ages, so their semantic modal diversities were justifiable in contemporary Persian, while the other two verbs of šodæn and xastæn had no modal usage in the Middle Ages. However, the verb of šodæn (to become) had a variety of modal meanings in contemporary Persian, the reasons of which needed further investigation, but xastæn (to want) like its equivalent, to reduce (kāmistan), had only one modal meaning on the axis of “possibility” in the Middle Persian.Comparison of the results of this study with those of the research conducted on some other Iranian languages, such as Kurdish Sorani (Moradi, 2013) and Hawrami (Naghzgoye Kohan & Naqshbandi, 2016) showed the diversity of meanings of the three verbs of bayestæn, tavanestæn, and šodæn in these languages. In this respect, Persian and these other two Iranian languages were almost similar with some differences. For example, in the case of Hawrami, Naghzgoo Kohan and Naghshbandi (2016) believed that the verb of šodæn (to become) had a meaning on both axes of possibility and necessity so that Hawrami violated the typological principle proposed by Nauze (2008), while the data of contemporary Persian language did not violate this principle. Moradi (2013) introduced "maybe" along with "should" as a verb in Sorani Kurdish. It seemed that "maybe" was adverbial in modern Persian, while it was a modal verb in the Middle Persian.  As Abdi (2021) claimed, the verbs of bayestæn, tavanestæn, and šodæn with their greatest semantic diversities had to be the most frequent modal verbs in modern Persian if there was a relationship between their diversity of meanings and frequency of a linguistic construct.Comparison of the results of the present study with those of Abdi's research revealed that this claim was true for the two verbs of bayestæn and tavanestæn, while Abdi introduced xastæn (to want) as the second most frequent verb in the spoken modern Persian and placed šodæn (to become) in a lower rank. There was an opposing variety of the modal meanings of these two verbs, indicating that šodæn had more semantic diversity than xastæn.